Involvement of the vagus nerve in the anorectic effect of monoacylglycerol acyltransferase 2 inhibition in mice - Kosuke Takemoto; Hideaki Kato; Kenichi Higashino (Wiley, 2023)
Abstract Background Many of the drugs used for obesity treatment have adverse effects on the central nervous system. Therefore, novel treatments, such as peripherally acting drugs, are needed. Monoacylglycerol acyltransferase 2 (MGAT2), highly expressed in the small intestine, catalyzes the first step of triacylglycerol re‐synthesis. MGAT2 inhibition suppresses food intake in high‐fat diet (HFD)‐fed mice, but the mechanisms remain unclear. Here, the involvement of the vagus nerve in MGAT2 inhibition‐induced feeding suppression was investigated. Methods Fasted mice were administered an MGAT2 inhibitor. Food intake was measured after HFD re‐feeding, and the effect of capsaicin pretreatment on changes in food intake was evaluated. The number of c‐fos‐positive cells in the nucleus tractus solitarius and levels of appetite regulators were determined after HFD re‐feeding or lipid gavage. Results The anorectic effect of the MGAT2 inhibitor was abolished when vagus nerve function was interrupted by capsaicin. MGAT2 inhibition increased the number of c‐fos‐positive cells in the nucleus tractus solitarius and elevated intestinal oleoylethanolamide, plasma peptide tyrosine-tyrosine and plasma glucagon‐like peptide‐1 levels. Conclusion MGAT2 inhibition suppresses feeding behavior via peripheral vagus nerve signaling and may serve as a novel anti‐obesity strategy with a low risk of unexpected central nervous system‐related adverse effects.